Pemberdayaan Kesehatan Ibu Hamil dengan Aplikasi Mindfulness Pregnancy - Kundarti, Finta Isti; Titisari, Ira; Rahayu, Dwi Estuning (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Mental health problems during pregnancy can cause complications in pregnancy. In Bandar Lor Village there are still many pregnant women who experience psychological problems. The purpose of this community service is to increase the understanding and skills of pregnancy mindfulness in pregnant women independently through online mindfulness pregnancy applications and hands-on exercises to increase self-empowerment in optimizing their mental health during pregnancy. Community service activities are carried out in 2x meetings with a distance of 2 weeks. Each meeting was held for 4 hours. Training was also given to 50 pregnant women. The skills provided are on how to use the application, and then train pregnant women in practicing mindfulness/meditation which includes mindful breathing awareness, mindfulness eating, loving-kindness meditation, prenatal yoga, body scanning with baby, sitting meditation, mindful walking, and silent meditation. The results of the interviews and post-tests obtained an increase in the understanding and skills of pregnant women regarding the use of mindfulness pregnancy applications, skills in meditation/mindfulness, and improving mental health. Suggestions for further community service activities are to develop wider community empowerment according to health problems that are currently developing in Indonesia.